2009
DOI: 10.1002/ejoc.200900825
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of Sulfur‐, Nitrogen‐ and Oxygen‐Containing Eight‐Membered Ring Lactams

Abstract: Bi(NO3)3‐catalyzed ring expansion of five‐membered ring 1,4‐diketones in the presence of primary amines leads to eight‐membered ring lactams. When applied to starting materials with a tetrahydrothiophene or pyrrolidine moiety, tetrahydro‐2H‐1,4‐thiazocin‐3‐ones and hexahydro‐1,4‐diazocin‐2‐ones are obtained as representatives of these very rare heterocyclic systems. In the case of tetrahydrofuran derivatives, other reaction conditions are required and yields of tetrahydro‐2H‐1,4‐oxazocin‐3‐ones are very low.(©… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Most of these are either intermolecular or deal with achiral substrates. [7] We were encouraged to apply the palladium catalyzed aromatic carbon-nitrogen bond forming reaction involving the cross coupling of aryl halides (or triflates, nonaflates, mesitylates) and amines which has recently seen an upsurge in interest as a useful synthetic tool. [8] Amination of aryl bromides under tin free conditions, initially achieved both by Buchwald [9a] and Hartwig [9b] groups, mainly focused on the intermolecular amination of aryl bromides or iodides to give substituted anilines.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these are either intermolecular or deal with achiral substrates. [7] We were encouraged to apply the palladium catalyzed aromatic carbon-nitrogen bond forming reaction involving the cross coupling of aryl halides (or triflates, nonaflates, mesitylates) and amines which has recently seen an upsurge in interest as a useful synthetic tool. [8] Amination of aryl bromides under tin free conditions, initially achieved both by Buchwald [9a] and Hartwig [9b] groups, mainly focused on the intermolecular amination of aryl bromides or iodides to give substituted anilines.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the scope of this re-action regarding the amine, we attempted to convert BnNH 2 , EtOCH 2 CH 2 NH 2 , iPrNH 2 , CyNH 2 , GlyOtBu, and β-AlaOtBu, [19] but only in the case of BnNH 2 was a product, 6c, obtained in low yield and low purity (Scheme 4, Table 1). Although we were convinced from our earlier work that the Bi-salt is required for the reaction, [11][12][13] when we attempted to convert ethyl ester 5b with MeNH 2 without Bi-additive, the product 6b was indeed formed. Again, several reaction parameters were screened, and it was found that conversion with two equivalents of amine at 100°C for 16 h gave optimal results, although the yield was still moderate (38 %).…”
Section: Resultsmentioning
confidence: 86%
“…The hitherto unknown oxoindanecarboxylates 5a and 5b, both containing a 1,4-diketone motif, were accessed starting from the corresponding β-oxo esters 4a [16] and 4b [17] and phenacyl bromide in good yields according to a standard protocol [13] previously used by us (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interconversion of the five-membered ring in starting materials 1 to an eight-membered ring in products 2 is assumed to proceed through intermediate 3 with a bicyclo [3.3.0] skeleton. [2] Furthermore, we have been able to convert tetrahydrothiophenes 1 (X = S) and pyrrolidines (X = N-PG) to respective thiazocinones 4 (X = S) [3] and diazocinones (X = N-R D ), [4] the latter having a fourth point of diversity R D , which was introduced after deprotection of secondary amine N-PG. [2] Furthermore, we have been able to convert tetrahydrothiophenes 1 (X = S) and pyrrolidines (X = N-PG) to respective thiazocinones 4 (X = S) [3] and diazocinones (X = N-R D ), [4] the latter having a fourth point of diversity R D , which was introduced after deprotection of secondary amine N-PG.…”
Section: Introductionmentioning
confidence: 99%